Shock metamorphism in Northwest Africa 8159, Tissint and Elephant Moraine A79001: implications for thermal histories and geochronology - Sharp, Thomas G.; Hu, Jinping; Walton, Erin L. (My University, 2016)
Shock metamorphic effects in Martian meteorites provide a record of recent impact events on Mars. The key to interpreting this record is understanding the shock conditions and relating these to impact processes. Martian meteorites have experienced shock effects, ranging from nearly unshocked (S1) to very highly shocked (S6). The shock effects observed are typically heterogeneous and local shock effects depend on pressure, deformation and thermal histories. In this study we examine shock pressures and thermal histories of three Martian meteorites and discuss implications for shock resetting of isotope systems. Each sample experienced a different P-Tt path, resulting in different textures and mineral assemblages.
Presented on August 7-12, 2016 at the Annual Meeting of the Meteoritical Society held at the Henry Ford Building in Berlin, Germany.
Keywords: Martian meteorites; shock